The High Prevalence of Colorectal Neoplasms in Preoperative Patients with Abdominal Aortic Aneurysm or Peripheral Artery Disease - Yamamoto, K.; Miyata, T.; Nagawa, H. (Eur J Vasc Endovasc Surg, 2007)
In Japan, the incidence of both colorectal carcinoma and vascular disease is increasing. We screened preoperative patients with abdominal aortic aneurysm (AAA) or peripheral artery disease (PAD) for colorectal cancer. This study was retrospective and cross-sectional. The subjects were 492 patients admitted for elective surgery of AAA or PAD. The patients underwent immunochemical faecal occult blood tests (FOBT) before operation, and those with positive results underwent investigations for colorectal neoplasm. We compared the results with that of screening programmes performed on the general population. Of the 408 patients that underwent FOBT, 104 (25.5%) were positive. After colonoscopy, six (1.5%) had colorectal carcinoma and 16 (3.9%) had advanced adenoma. These values were several folds higher than that for the general population in Japan. Patients with AAA or PAD carry a high risk for colorectal neoplasm.